2021
DOI: 10.21037/atm-21-2076
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating glucose metabolism by Fbxw7 promotes Taxol sensitivity of colon cancer cells through downregulating NADPH oxidase 1 (Nox1)

Abstract: Background: Colorectal cancer (CRC), one of the most common malignancies worldwide, is associated with poor survival and has a high mortality rate. Taxol is a chemotherapeutic agent that has been clinically applied as a first-line drug against diverse cancers. Yet, development of drug resistance has become the major challenge for anti-cancer treatments. F-box and WD40 domain protein 7 (Fbxw7) is a known tumor suppressor which is frequently downregulated in cancers. However, the biological roles and mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Notably, the study showed that Hace2 directly targeted Rac1, but not NADPH oxidase. Another E3 ligase Fbxw7 can directly bind to and degrade NADPH oxidase 1 (Nox1) ( Wang et al 2021 ). RNF34 ablation was also reported to enhance the generation of NADPH oxidase-dependent ROS ( Fang et al 2021 ).…”
Section: Ubiquitination Regulates Responses To Intercellular Stressesmentioning
confidence: 99%
“…Notably, the study showed that Hace2 directly targeted Rac1, but not NADPH oxidase. Another E3 ligase Fbxw7 can directly bind to and degrade NADPH oxidase 1 (Nox1) ( Wang et al 2021 ). RNF34 ablation was also reported to enhance the generation of NADPH oxidase-dependent ROS ( Fang et al 2021 ).…”
Section: Ubiquitination Regulates Responses To Intercellular Stressesmentioning
confidence: 99%
“…The inhibition or knockout of HDAC6 reduced glycolytic metabolism in triple-negative breast cancers [ 128 ]. The inhibition of 6-Phosphofructo-2-Kinase/Fructose-2,6-Biphosphatase 3 (PFKFB3) enhanced the sensitivity of NSCLCs to erlotinib by decreasing autophagy [ 129 ], and inhibiting glycolysis was shown to overcome taxol-resistance in colorectal cancer cells [ 130 ]. These reports suggest that autophagy increases the expression of HDAC6, which in turn enhances glycolysis and anti-cancer drug resistance.…”
Section: Role Of Hdac6 In Autophagymentioning
confidence: 99%
“…• NOX1 promotes resistance to Taxol (a chemotherapeutic agent) in colon cancer cells, and such NOX1 tumorigenic effects can be overriden via glycolysis inhibition. In addition, NOX1 is negative regulated by the tumor suppressor FBXW7 in colon cancer [113].…”
Section: Nox1mentioning
confidence: 99%